A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 3 years ago
Use the substitution method to solve the following system of equations.
3x – y = 2
6x – 2y = 4
anonymous
 3 years ago
Use the substitution method to solve the following system of equations. 3x – y = 2 6x – 2y = 4

This Question is Closed

anonymous
 3 years ago
Best ResponseYou've already chosen the best response.0This method requires that you rewrite one of the equations as y = ?? or x = ??. from there you substitute that equation for the variable into the 2nd equation. In this case , rewrite the first one and solve for Y. Once I see that, I will further explain next steps

zpupster
 3 years ago
Best ResponseYou've already chosen the best response.0y=3x2 6x2y =4 6x2(3x2) = 4 6x6x +4 = 4 4=4 this is a true statement

anonymous
 3 years ago
Best ResponseYou've already chosen the best response.0zpupster  that is not the directions. I think what you were trying to say is that there is no solution. My question  is this consistent or inconsistent.
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.